PERAN PENYULUH PERTANIAN DALAM PEMBERDAYAAN KELOMPOK TANI DI DESA AMPERA KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN - Karniyati, Ani; Suhardi, Suhardi; Sangadji, Suwandi S. (EDUTECH CONSULTANT, 2019)
This study aims to determine the effect of the role of agricultural extension agents in empowering farmer groups in Ampera Village, Oba District, North Tidore Islands City. This research was conducted by survey, the research locations in Ampera Village were selected purposively. The method used in this study is a correlational method that describes the influence of variables X and Y variables. The population in this study were all members of the farmer group in Ampera Village which amounted to 67 people, while the sample in this study amounted to 67 with the sampling technique was census or saturated sampling. The time of the study was in November 2018 to December 2018. The data used were primary data resulting from questionnaire distribution on 67 people. The analytical method used is a quantitative method. Analysis of related data using regression and correlation statistical tests. The results showed that the role of agricultural extension agents had a significant effect on the empowerment of farmer groups.